Corporate innovative technologies: essence and concepts - M. I. Fedotov; I. V. Penkova; M. D. Ovsyanko (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. In modern conditions, the innovative activity of Russian enterprises requires the improvement of both practical tools for intensifying the development and implementation of innovations, and a revision of the theoretical and methodological apparatus in the field of corporate innovation management.Goal. The study aims to identify the essence and reveal the key concepts which define corporate innovative technologies. Based on the analysis of theoretical approaches, the key features of innovations that determine their essence are highlighted. Firstly, organizational, legal, financial and other support from the state. Secondly, the implementation of two basic approaches to the concept of “innovation”: innovation seems to be the result of human intellectual and creative activity, and it is the result of the introduction of a certain innovation in a specific practical activity. Thirdly, the protective legal and individual essence of innovation in the context of organizational and legal relations is manifested in the individual initiative of the inventor. Fourthly, innovation is aimed at increasing the efficiency of corporate activities. Fifthly, the latent essence ofinnovation in the corporate development of a company's rationalization resource is characterized by the possibility of manifestation of hidden innovation.Materials and methods. The analysis was carried out on the basis of materials from monographic studies, scientific publications, analytical reports, statistical data, materials from legislative and legal documents. There were applied methods of comparative analysis and synthesis.Results and discussion. The place and role of innovation in the modern economic system of Russia is analyzed. The key elements that determine the essence of innovation have been identified. Based on the analysis of theoretical approaches, the key features of innovations that determine their essence are highlighted.Conclusion. The essence of innovation is determined by elements of a strategic, creative, practical, protective-legal, individual, economic, and potential nature. At the same time, the priority role of the potential (resource) essence of innovation is noted. The analysis of the key features of corporate innovative technologies revealed their interconnectedness and the priority of the latent (potential) essence of innovation, since all other features depend on the implementation of the company's innovative potential. Without the subject of innovation activity having the minimum creative (personnel), instrumental, information-rationalization, etc. necessary resource, taking into account external factors of influence, the implementation of the life cycle of innovation is impossible.